2019
DOI: 10.1007/s10815-019-01414-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanded genetic carrier screening in clinical practice: a current survey of patient impressions and attitudes

Abstract: Purpose Expanded genetic carrier screening (ECS) is an important part of gynecological practice and preconception planning. We evaluated the awareness and attitudes among women regarding ECS and factors that may influence decision-making in a family planning context. Methods A 32-question survey in an academic university practice was given to 521 women who were either currently pregnant (n = 108), undergoing gynecologic care who were considering future fertility (n = 308), and considering or receiving fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…One study that investigated the impact of ECS showed that respondents with negative test results generally did not experience long-term negative emotional impact, and only reported heightened anxiety while waiting for the test results [ 13 ]. Additional studies have shown that the information from ECS could relieve uncertainty and anxiety [ 17 ], was of value to participants [ 11 , 18 ] and led to informed reproductive decision making [ 19 ]. Reasons to have ECS among both high-risk groups and the general population need further investigation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study that investigated the impact of ECS showed that respondents with negative test results generally did not experience long-term negative emotional impact, and only reported heightened anxiety while waiting for the test results [ 13 ]. Additional studies have shown that the information from ECS could relieve uncertainty and anxiety [ 17 ], was of value to participants [ 11 , 18 ] and led to informed reproductive decision making [ 19 ]. Reasons to have ECS among both high-risk groups and the general population need further investigation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IEMs included in ECS panels generally have a progressive course. Previous studies in the USA, Sweden and the Netherlands have investigated the opinions of the general population toward universal preconception ECS and reported that between 30% and 34% of the respondents would consider to use preconception ECS [ 10 12 ]. The study by Ong et al, conducted in Australia, showed that genetic knowledge, i.e., baseline knowledge on genetics, is instrumental in influencing ECS participation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them felt positive or neutral towards ECS while half reported no interests in testing. If they were screened to be positive carriers, around 50% of them would not proceed with the sequential testing of their partners [ 28 ]. There are multiple factors affecting attitudes and opinions towards ECS held by patients, such as familiarity with genetic conditions, residual risk of diseases screened, stress from testing, and financial concerns [ 29 ].…”
Section: Discussionmentioning
confidence: 99%